Chemopreventive effect of dieckol against 7, 12‐dimethylbenz(a)anthracene induced skin carcinogenesis model by modulatory influence on biochemical and antioxidant biomarkers. Issue 5 (21st December 2020) - Xiao, Wenming; Liu, Hongyan; Lei, Ying; Gao, Huawei; Alahmadi, Tahani Awad; Peng, Haitao; Chen, Wei
ABSTRACT: Skin cancer is the commonly found type, which contributes to 40% of whole cancer incidences worldwide. Dieckol is an active compound occurs in the marine algae with many biological benefits. In this exploration, we intended to investigate the therapeutic potency of dieckol against the 7, 12‐dimethylbenz(a)anthracene (DMBA)‐triggered skin carcinogenesis in mice. The skin cancer was stimulated to the animals via injecting the 25 μg of DMBA in 100 μL of acetone in shaved dorsal portion along with the 30 mg/kg of dieckol supplementation for 25 week. The antioxidant enzymes and phase‐I and –II detoxifying enzymes in the test animals were inspected via standard protocols. Pro‐inflammatory markers (IL‐6, IL‐1β, and TNF‐α) level was examined via ELISA kits and the expression of inflammatory molecular markers like p‐NF‐ƙB, IƙBα and p‐IƙBα were studied through western blotting. The expression status of pro‐ and anti‐apoptotic proteins (p53, Bax, Bcl‐2, caspase‐3, caspase‐9, COX‐2, TGF‐β1) was investigated via real‐time polymerase chain reaction (RT‐PCR). Our results revealed that the 30 mg/kg of dieckol supplementation noticeably regained the body and liver weight and also diminished the tumor incidence in the DMBA‐incited animals. Dieckol treatment exhibited an enhanced antioxidants (SOD, CAT, GPx, and GSH) and reduced phase‐I enzymes Cyt‐p450 and Cyt‐b5 in the DMBA‐induced animals. Dieckol also diminished the pro‐inflammatory modulators like IL‐6, IL‐1β and TNF‐α. Western blotting result evidenced that the dieckol was inhibited the IƙB/NF‐ƙB signaling pathway. RT‐PCR study proved the enhanced expression of pro‐apoptotic protein (p53, Bax, caspase‐3 and ‐9) in the dieckol treated animals. Histological study also confirmed the therapeutic benefits of Dieckol. Altogether with these findings, it was clear that the dieckol has appreciably allayed the DMBA activated skin tumorigenesis in the mice and it could be a promising agent to treat the human skin cancer in future.